3D Numerical simulation of turbulent flow and heat transfer in a U-tube of different configurations - S. Mushatet, Khudheyer; Ali M, Ayad (International Journal of Engineering and Technology, 2018)
In this work, three-dimensional incompressible turbulent flow and heat transfer in a tube of U-configuration has been investigated numerically. The influence using the U-tube in various cross-sectional shape, on thermal and hydrodynamic fields are presented in details. The cases of study for the U-tube are tested, by using the tube with different cross-sectional shapes (square and rectangle) and compare them with a circular cross-sectional shape, with a constant cross-sectional area and curvature radius ratio. The tube surface is subjected to a constant heat flux and the air is chosen to be the working fluid with turbulent flow under a range of Reynolds number (10000 to 25000). The turbulent flow and heat transfer is governed by continuity, momentum and energy equations. The effect of turbulence is treated by a k-ℇ turbulent model. ANSYS fluent code (15.0) based on finite volume method is used to get the numerical results. The flow separation and vortex formation at the bend section plays major role in heat and momentum transfer in bend tube. The obtained results of using of square and rectangular cross-sectional shape reduces the Nusselt number by 21.6% and 16.3% respectively as compared with the circular cross-section U-tube (the same circular cross-sectional area), and considerable decrease of the friction factor by 7.4% and 5.9% as compared with the circular cross-section U-tube. Numerical investigations indicated that within the circular cross-section U-tube a significant heat transfer enhancement is observed. In addition, the velocity fields for the primary and secondary flows were showed in a vector diagram. The present numerical results are compared with empirical correlations and verified a comparatively good agreement. The numerical method was validated by comparing the results with the experimental data and showed acceptable agreement.